Intriguing Games to Enhance Students` Understanding of the Morphology Materials - Wahab Syakhirul Alim; Lasmi Febrianingrum (Edukasi, 2020)
The study aimed to enhance students` understanding of the morphology material through intriguing games. We conducted this research on the students at Tadris Bahasa Inggris IAIN Madura in 2019/2020 with 37 students. This report used the design of classroom action research (CAR) with interviews, observation, and questionnaires as the instrument to gain the data. We carried the CAR out based on Kurt. L style, they are planning, acting, observing, and reflecting. Throughout this report, the researchers carried out collaborative action research. The study results showed the average score of the pre-test is 58.8%, and the post-test score reached up to 74.1% by 29 students of 37 students who pass the completeness (reached for minimum score) in cycle I. For cycle II, it reached up to 81.1% or raised gradually from 19% to 26%, 35 students from 37 who pass the completeness in cycle II. Besides, convincingly, implementing an intriguing game can make the students interested in learning, easy to understand, motivated to study more, and become competitive.